Phenomenology and Connectionism - Yoshimi, Jeffrey K. (Frontiers in Psychology, 2011)
I show how the dynamics of consciousness can be formally derived from the “open dynamics” of neural activity, and develop a mathematical framework for neuro-phenomenological investigation. I describe the space of possible brain states, the space of possible conscious states, and a “supervenience function” linking them. I show how this framework can be used to associate phenomenological structures with neuro-computational structures, and vice-versa. I pay special attention to the relationship between (1) the relatively fast dynamics of consciousness and neural activity, and (2) the slower dynamics of knowledge update and brain development.